Long term results of postoperative Intensity-Modulated Radiation Therapy (IMRT) in the treatment of Squamous Cell Carcinoma (SCC) located in the oropharynx or oral cavity - Hoffmann, Michael; Saleh-Ebrahimi, L.; Zwicker, F.; Haering, P.; Schwahofer, A.; Debus, Jürgen; Huber, Peter E.; Roeder, F. (Radiation oncology, 2015)
To report our long-term results with postoperative intensity-modulated radiation therapy (IMRT) in patients suffering from squamous-cell carcinoma (SCC) of the oral cavity or oropharynx.
Gesehen am 07.09.2020